Classroom Management of Christian Religious Education During the Covid-19 Pandemic - Sianipar, Desi; Hasugian, Johanes Waldes; Sairwona, Wellem; Zega, Yunardi Kristian; Ritonga, Nova (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
During the covid-19 Pandemic that hit Indonesia, online learning became a learning model that must be done in areas with a high covid-19 spread rate. There are many challenges faced by all interested parties in the world of education. Problems include limited internet access, skills in using technology, and the ability to manage online learning classes. This study focuses on the role of Christian Religious educators or teachers in overcoming online learning problems and challenges by seeking to create a conducive and enjoyable learning atmosphere and quality so that students can learn well and achieve learning outcomes. Therefore, the purpose of this study is to describe the concept of effective online classroom management for Christian religious education learning to shape the Christian character of students during the covid-19 pandemic based on five classroom management functions, namely leading, planning, organizing,  and evaluation. In order to achieve this goal, this research is qualitative-descriptive. That is, it describes data regarding Christian religious education class management during the covid-19 pandemic. The results of this study are that online classroom management for Christian religious education learning can be realized through the leadership of teachers who are servant-hearted; planning of learning activities in shaping Christian character; setting the learning process and learning materials; teacher skills in implementing learning; and teachers who always guarantee the quality of their learning through evaluation activities.